Bonding of universal adhesives to dentine – Old wine in new bottles?. Issue 5 (May 2015) - Chen, C.; Niu, L.-N.; Xie, H.; Zhang, Z.-Y.; Zhou, L.-Q.; Jiao, K.; Chen, J.-H.; Pashley, D.H.; Tay, F.R.
Abstract Objective Multi-mode universal adhesives offer clinicians the choice of using the etch-and-rinse technique, selective enamel etch technique or self-etch technique to bond to tooth substrates. The present study examined the short-term in vitro performance of five universal adhesives bonded to human coronal dentine. Methods Two hundred non-carious human third molars were assigned to five groups based on the type of the universal adhesives (Prime&Bond Elect, Scotchbond Universal, All-Bond Universal, Clearfil Universal Bond and Futurabond U). Two bonding modes (etch-and-rinse and self-etch) were employed for each adhesive group. Bonded specimens were stored in deionized water for 24 h or underwent a 10, 000-cycle thermocycling ageing process prior to testing (N = 10). Microtensile bond testing (μTBS), transmission electron microscopy (TEM) of resin–dentine interfaces in non-thermocycled specimens and scanning electron microscopy (SEM) of tracer-infused water-rich zones within hybrid layers of thermocycled specimens were performed. Results Both adhesive type and testing condition (with/without thermocycling) have significant influences on μTBS. The use of each adhesive in either the etch-and-rinse or self-etch application mode did not result in significantly different μTBS to dentine. Hybrid layers created by these adhesives in the etch-and-rinse bonding mode and self-etch bonding mode were ∼5 μm and ≤0.5 μm thick respectively. Tracer-infused regions could be identified within the resin–dentine interface from all the specimens prepared. Conclusion The increase in versatility of universal adhesives is not accompanied by technological advances for overcoming the challenges associated with previous generations of adhesives. Therapeutic adhesives with bio-protective and bio-promoting effects are still lacking in commercialized adhesives. Clinical significance Universal adhesives represent manufacturers' attempt to introduce versatility in product design via adaptation of a single-bottle self-etch adhesive for other application modes without compromising its bonding effectiveness.